Effects of vitamin E on peroxisome proliferator-activated receptor gamma and nuclear factor-erythroid 2-related factor 2 in hypercholesterolemia-induced atherosclerosis - SÖZEN, AHMET ERDİ; YILMAZ, BETÜL; KARTAL ÖZER, NESRİN (ELSEVIER SCIENCE INC, 2014)
Atherosclerosis and associated cardiovascular complications such as stroke and myocardial infarction are major causes of morbidity and mortality. We have previously reported a significant increase in mRNA levels of the scavenger receptor CD36 in aortae of cholesterol-fed rabbits and shown that vitamin E treatment attenuated increased CD36 mRNA expression. In the present study, we further investigated the redox signaling pathways associated with protection against atherogenesis induced by high dietary cholesterol and correlated these with CD36 expression and the effects of vitamin E supplementation in a rabbit model. Male albino rabbits were assigned to either a control group fed with a low vitamin E diet alone or a test group fed with a low vitamin E diet containing 2% cholesterol in the absence or presence of daily intramuscular injections of vitamin E (50 mg/kg). To elucidate the mechanisms by which vitamin E supplementation alters the effects of hypercholesterolemia in rabbit aortae, we measured peroxisome proliferator-activated receptor gamma (PPAR gamma), ATP-binding cassette transporter A1 (ABCA1), and matrix metalloproteinase-1 (MMP-1) mRNA levels by quantitative RT-PCR and the expression of MMP-1, nuclear factor-erythroid 2-related factor 2 (Nrf2), and glutathione S-transferase alpha (GST alpha) protein by immunoblotting. The increased MMP-1 and decreased GSTa expression observed suggests that a cholesterol-rich diet contributes to the development of atherosclerosis, whereas vitamin E supplementation affords protection by decreasing MMP-1 and increasing PPAR gamma, GSTa, and ABCA1 levels in aortae of rabbits fed a cholesterol-rich diet. Notably, protein expression of Nrf2, the antioxidant transcription factor, was increased in both the cholesterol-fed and the vitamin E-supplemented groups. Although Nrf2 activation can promote CD36-mediated cholesterol uptake by macrophages, the increased induction of Nrf2-mediated antioxidant genes is likely to contribute to decreased lesion progression. Thus, our study demonstrates that Nrf2 can mediate both pro- and antiatherosclerotic effects. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Atherosclerosis; Hypercholesterolemia; Nrf2; PPAR gamma; Redox signaling; Vitamin E; Free radicals; LOW-DENSITY-LIPOPROTEIN; SMOOTH-MUSCLE-CELLS; ENDOTHELIAL-CELLS; OXIDATIVE STRESS; GENE-EXPRESSION; PPAR-GAMMA; CARDIOVASCULAR-DISEASE; DEFENSE PATHWAY; NRF2 ACTIVATION; DEFICIENT MICE